Chromatic total domination in graphs. (4th July 2019) - Balamurugan, S.; Anitha, M.; Eswari, M. Angala; Kalaiselvi, S.
Abstract: Let G = ( V, E ) be a simple, finite and undirected graph and without isolated vertex. A set D ⊆ V is said to be chromatic total dominating set of G if D is a total dominating set and χ (< D >) = χ ( G ). The minimum cardinality of a chromatic total dominating set of G is called the chromatic total domination number of G and is denoted by γ t ch ( G ). In this paper, we discuss the chromatic total domination number for standard graphs.